Reading comprehension and learning of the english language at the basic level - Guzmán Soto, Doris G. (2022)
The main objective of the research was to determine the relationship of reading comprehension with the learning of the English Language at the basic level of the Language Center - UNHEVAL - 2017; in order to know if the progress of Reading, Writing and Grammar are related to reading comprehension in Basic Level VI students. The study was descriptive, prospective and cross-sectional, with a correlational design; The sample consisted of 22 students from the sixth cycle - basic level of the English language; A test was applied for each of the dimensions studied. The results showed that, of the total number of students, they presented a level of reading comprehension "At the beginning" of 9.1%; 40.9% “In process” and 50% “In anticipated achievement” and neither obtained the outstanding achievement. It was concluded that the level of English language learning is related to reading comprehension; Likewise, it was evidenced that the greater the learning of writing, grammar and reading, the better the level of reading comprehension.